2020
DOI: 10.1002/lsm.23215
|View full text |Cite
|
Sign up to set email alerts
|

First Assessment of a Carbon Monoxide Laser and a Thulium Fiber Laser for Fractional Ablation of Skin

Abstract: Background and Objectives A recent generation of 5,500 nm wavelength carbon monoxide (CO) lasers could serve as a novel tool for applications in medicine and surgery. At this wavelength, the optical penetration depth is about three times higher than that of the 10,600 nm wavelength carbon dioxide (CO2) laser. As the amount of ablation and coagulation is strongly influenced by the wavelength, we anticipated that CO lasers would provide extended coagulation zones, which could be beneficial for several medical ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 30 publications
1
8
0
2
Order By: Relevance
“…Good results have been achieved in patients with depressed scars. The newly drilled holes will not overlap each other, and fractional laser treatment will only cover part of the skin tissue, and normal skin will be preserved, speeding up recovery (20). It can stimulate the proliferation of collagen fibers at the base, grind and remove the sharp edges of concave scars, flattens the concave part, remove and alleviate concave scars, accelerate the healing speed (21), and improve the treatment effect.…”
Section: Original Articlementioning
confidence: 99%
“…Good results have been achieved in patients with depressed scars. The newly drilled holes will not overlap each other, and fractional laser treatment will only cover part of the skin tissue, and normal skin will be preserved, speeding up recovery (20). It can stimulate the proliferation of collagen fibers at the base, grind and remove the sharp edges of concave scars, flattens the concave part, remove and alleviate concave scars, accelerate the healing speed (21), and improve the treatment effect.…”
Section: Original Articlementioning
confidence: 99%
“…= (0); (15) = * (0); (13) = 6 ∫ ℜ ()ℜ ()∞ 0 ; (14) = ℌ ˎ (0); (15) = ℌ * ˎ (0); (9) = 7 ∫ ℜ ()ℑ (); (10) = (0…”
Section: Methodsunclassified
“…(3) − 3 ( 11 (4) 11 (6) + 11 ( 7) 11 (9) ); ℳ 11 (6) = 11 ( 7) 11 (8) + 3 11 ( 12) 11 (14) ; ℳ 11 (7) = 11 ( 9) 11 (10) + 2 11 ( 12) 11 (14) ; ℳ 11 (8) = 1 11 ( 9) 11 (11) + 11 ( 12) 11 (13) ; 11 (6) = 11 ( 7) 11 (8) + 3 11 ( 12) 11 (14) ; 11 (7) = 11 ( 9) 11 (10) + 2 11 ( 12) 11 (14) ; 11 (8) = 11 (12) 11 (13) + 1 11 ( 9) 11 (11) ; Ӄ (7) = 11…”
Section: Methodsunclassified
See 1 more Smart Citation
“…It was concluded that the wound‐healing process after TMA is much faster, and the recovery time minimizes significantly compared to other ablative techniques. The investigation of coagulation characteristics and ablation of a new CO laser and a high-power Tm:fiber laser were presented to assess their potential application for fractional ablation of the skin 14 . The use of a CO laser showed approximately two times larger coagulation zones than the CO 2 laser.…”
Section: Introductionmentioning
confidence: 99%